Local Education Policies - Hudson, C. author. aut Link
XVIII, 243 p.
Keywords: In the Western world, education policy has increasingly become a local matter. Localities and schools adjust education to meet specific local needs, fragmentation and diversity. Globalization and the greater emphasis on knowledge in society however, also embody strong streamlining tendencies. This edited volume examines and compares the way in which local education systems in Britain and Sweden are created in the interplay between common tendencies of change and particular local conditions.